Expression and Purification of the Human Voltage-Gated Proton Channel (hHv1) - Emerson Carmona; D. Marien Cortes; Luis Cuello (Bio-Protocol)
The voltage-gated proton channel (Hv1) is a membrane protein that dissipates acute cell proton accumulations. To understand the molecular mechanisms explaining Hv1 function, methods for purifying the protein are needed. Previously, methods were developed for expressing and purifying human Hv1 (hHv1) in yeast and later in bacteria. However, these methodologies produced low protein yields and had high production costs, considerably limiting their usefulness. The protocol described in this work was developed to overcome those limitations. hHv1 is overexpressed in bacteria, solubilized with the detergent Anzergent 3–12, and purified by immobilized metal affinity chromatography (IMAC) and size-exclusion chromatography (SEC). Our protocol produced higher protein yields at lower costs than previously published methodologies.